Anti-inflammatory effect of Irisin on LPS-stimulated macrophages through inhibition of MAPK pathway - Ma, Y; Du, Y; Yang, J; He, Q; Wang, H; Lin, X (Physiological research, 2023)
This study aimed to investigate the effect of irisin on LPS-induced inflammation in RAW 264.7 macrophages through inhibition of the mitogen-activated protein kinase (MAPK) pathway. A network pharmacology-based approach, combined with molecular docking and in vitro validation were performed to identify the biological activity, key targets, and potential pharmacological mechanisms of irisin against LPS-induced inflammation. By matching 100 potential genes of irisin with 1893 ulcerative colitis (UC) related genes, 51 common genes were obtained. Using protein-protein interaction networks (PPI) and component-target network analysis,10 core genes of irisin on UC were further identified. The results of gene ontology (GO) enrichment analysis showed that the molecular mechanisms of irisin on UC were mainly related to major enrichment in the categories of response to xenobiotic stimulus, response to the drug, and negative regulation of gene expression. Molecular docking results showed good binding activity for almost all core component targets. More importantly, MTT assay and flow cytometry results showed that LPS-induced cytotoxicity was reversed by irisin, after coincubation with irisin, the level of IL-12 and IL-23 decreased in LPS-stimulated RAW264.7 macrophages. Irisin pretreatment significantly inhibited the phosphorylation of ERK and AKT and increased the expression of PPAR alpha and PPAR gamma. LPS-induced enhancement of phagocytosis and cell clearance were reversed by irisin pretreatment. Irisin ameliorated LPS-induced inflammation by inhibiting cytotoxicity and apoptosis, and this protective effect may be mediated through the MAPK pathway. These findings confirmed our prediction that irisin plays an anti-inflammatory role in LPS-induced inflammation via the MAPK pathway.
Keywords: lipopolysacharidy; makrofágy; fibronektiny; zvířata; zánět; Mice; Animals; ulcerózní kolitida; Lipopolysaccharides; Molecular Docking Simulation; Colitis, Ulcerative; Fibronectins; Mitogen-Activated Protein Kinases; RAW 264.7 Cells; simulace molekulového dockingu; Macrophages; mitogenem aktivované proteinkinasy; Inflammation; RAW 264.7 buňky; myši